WorldFish’s innovation catalog - Marwaha, Nisha; Ceccarelli, Valentina; Burcham, Lauren; Cullhaj, Megi (WorldFish, 2022)
This document contains a collection of major innovation journeys delivered by WorldFish in collaboration with various partners in the effort of targeting some of the major development challenges in aquatic food systems. To facilitate the reader in identifying the geographies and the contribution to the various impact areas, the collection has been organized following a geographic order by region and then countries. There are colored dots next to titles in the table of contents and marking each page (right top corner) specify the contribution to the most significant impact area, as per the WorldFish 2030 Strategy.